The Effectiveness of Advertising Marketing in Print Media during the Covid 19 Pandemic in the Mandailing Natal Region - Al Bara; Faisal Affandi; Ahmad Salman Farid; Datuk Imam Marzuki (Budapest International Research and Critics University, 2021)
This study explains how effective advertising marketing is in three print media in Mandailing Natal. Several print media such as the Waspada Daily, representatives of the Mandailing Natal bureau and Mohganews, stated that the impact of the Covid 19 outbreak on the effectiveness of advertisements in the print media mentioned above. On the other hand, the print media Madina Post revealed that the Covid 19 pandemic had little impact on the advertisements served through the advertising column in its print media. This study uses the principles of a qualitative approach, using the SOR theory as an acronym for Stimulus-Organism-Response which has an impact on the Covid 19 pandemic outbreak. Namely, humans whose souls include components; attitudes, opinions, behavior, cognition and conation.